Maternal persistent marijuana use and cigarette smoking are independently associated with shorter gestational age. Issue 6 (30th June 2020) - Nawa, Nobutoshi; Garrison‐Desany, Henri M.; Kim, Yoona; Ji, Yuelong; Hong, Xiumei; Wang, Guoying; Pearson, Colleen; Zuckerman, Barry S.; Wang, Xiaobin; Surkan, Pamela J.
Abstract: Background: Research assessing the effects of marijuana use on preterm birth has found mixed results, in part, due to lack of attention to the role of maternal tobacco smoking during pregnancy. Objectives: The study objective was to investigate whether maternal marijuana use was independently associated with gestational age, preterm birth, and two preterm birth subtypes (spontaneous vs clinician‐initiated). Methods: Participants included 8261 mother‐newborn pairs from the Boston Birth Cohort. Information on gestational age was collected from electronic medical records. Marijuana use and tobacco smoking during pregnancy were assessed through a standard questionnaire after birth. Linear and log‐linear regression models were used to assess associations between marijuana use with and without tobacco smoking during pregnancy and the outcomes of interest. Results: Of the 8261 mothers, 27.5% had preterm births. About 3.5% of mothers with term deliveries and 5.2% of mothers with preterm births used marijuana during pregnancy. Marijuana use and cigarette smoking were independently associated with a decrease in gestational age by 0.50 weeks (95% confidence interval [CI] −0.87, −0.13) and 0.52 weeks (95% CI −0.76, −0.28), respectively. Marijuana use during early or late pregnancy was associated with a similar decrease in gestational age by 0.50 weeks. When we examined the effects on the preterm birth subtypes, simultaneous marijuana use and tobacco smoking were associated with higher risk of spontaneous preterm birth (RR 1.64, 95% CI 1.23, 2.18). The elevated risk was not observed with clinician‐initiated preterm birth. Conclusions: In this high‐risk US population, maternal marijuana use and cigarette smoking during pregnancy were independently associated with shorter gestational age. When we examined the effects on preterm birth subtypes, the elevated risk was only observed with spontaneous preterm birth.